OWLS-CSM: A Service Profile Based Similarity Framework for Web Service Discovery - Naji Hasan.A.H; Gao Shu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
This paper presents OWLS-CSM framework, an OWL-S Service Profile based framework for web service discovery in cloud environment. In the proposed framework, services are presented as advertisements; their concepts are semantically defined and described in a hierarchal ontology to facilitate service matchmaking. In matchmaking process advertisements and query are represented as objects and three levels of similarities are used, based on OWL-S Service Profile, to matching, namely taxonomical similarity, functional similarity and non-functional similarity. Milestone method is adopted in the matchmaking algorithm to match the concepts according to their position in the hierarchal ontology. The results obtained from OWLS-CSM are analyzed and compared with other similar works to prove and evaluate the efficiency of our work.